Preparation of samarium iron garnet nanoparticles via modified conventional mixing oxides method - Al-Habashi, Ramadan Masoud; Abbas, Zulkifly (Trans Tech Publications, 2014)
This work is concerned with the preparation of samarium iron garnet (Sm3Fe5O12) nanoparticles via an improved technique named: Modified Conventional Mixing Oxides (MCMO) method. This material was characterized by XRD, FESEM, EDX and TEM. Metal oxides and ethanol solution were used as raw materials to prepare Sm3Fe5O12 (SmIG) material. Single-phase SmIG nanoparticles with an average particle value of 25 nm and average crystallite size value of 44 nm have been synthesized at 1350 °C via the MCMO method. SmIG powders with grain sizes below 1 μm and high purity have been presented by FESEM and EDX results, respectively. Lattice constant value of 12.535 A° and density value of 6.221 g.cm-3, were calculated for the SmIG sample. The latter has reached around 99% of its theoretical density. The MCMO method appears to be an attractive route due to the enhancement of structural properties of the interested sample with high yield in the nano-scale product as compared to other preparation techniques.